Analisis Efektivitas Musyawarah Perencanaanpembangunan - Ezi Hendri; Ninuk Purnaningsih; Amiruddin Saleh (Jurnal Komunikasi Pembangunan, 2014)
ABSTRACTDevelopment Planning Conference (Musrenbang) is a government program that aims for the community development programs related to a region. The purpose of this study is to look at the effectiveness of Musrenbang forum on villagelevel (Musrenbangkel). This research was conducted in March to April 2014 in the Village Pabuaran, Cibinong subdistrict, Bogor regency with the total respondents were 51 people. The hypothesis was tested with Spearman rank correlation. Correlation coefficient results showed that the effectiveness Musrenbangkel forum  as measured by three indicators, namely productivity, satisfaction, and morale is high. While gender relations, the characteristics of the group, guiding role and level of participation of group members is relatively good with moderate to very high category.Keywords: effectiveness, Musrenangkel, participation